A switching capacitor based multi‐port bidirectional DC–DC converter. Issue 9 (13th May 2021) - Shayeghi, Hossein; Pourjafar, Saeed; Hashemzadeh, Seyed Majid
Abstract: This paper introduces a novel bidirectional multi‐port DC–DC converter recommended for electric vehicle applications. The proposed structure has three ports with bidirectional features which can be operated in both step‐up and step‐down modes. This converter can supply the load from two independent voltage sources and can obtain a high voltage conversion ratio in both step‐up and step‐down operations. The low voltage stress throughout the power switches, high efficiency, and low components count are the characteristics of the proposed topology. For demonstrating the proposed structure's performance, the principle of operation modes, steady‐state analysis, and comparison results with other similar works are provided. Finally, an experimental prototype is built with a 120 W power level at 50 kHz operating, which validates the suggested converter's effectiveness and bidirectional trait. The suggested converter's efficiency in boost and buck mode is obtained about 94.2% and 94.37%, respectively that makes this converter to be used in renewable energy systems and electric vehicles with hybrid energy sources.